Activity of soil fluorescein diacetate (FDA) hydrolase under long-term fertilization - MA Xing-zhu (浙江大学学报. 农业与生命科学版)
The activities of fluorescein diacetate (FDA) hydrolase in black soil and brown soil under different long-term fertilization experiments were determined by the spectrophotometric method and using fluorescein diacetate (FDA) as the substrate. Results showed that there was a significant increase of hydrolase activity under combination treatment of organic manure with chemical fertilizers in black soil and brown soil, compared with the control, which were increased by 68.8% and 72.4%, respectively, and also were significantly higher than those under chemical fertilizer treatment. FDA hydrolase activity was highly significantly and positively correlated with soil microbial biomass carbon, and the correlation coefficients in black soil and brown soil were 0.912* * and 0.871* *, respectively. FDA hydrolase activity as an indicator of microbial activity, also could be used to evaluate the amount and activity of soil microorganism. Meanwhile, FDA hydrolase activity was also highly significantly correlated with other enzyme activities which participated in the nutrient cycles of C, N, P, S.